Quantitative Structure-Activity relationship, Molecular Docking and ADMET Screening of Tetrahydroquinoline Derivatives as Anti-Small Cell Lung Cancer Agents - Erazua, Ehimen Annastasia; Oyebamiji, Abel Kolawole; Akintelu, Sunday Adewale; Adewole, Pelumi Daniel; Adelakun, Adedayo; Adeleke, Babatunde Benjamin (Eclética Química, 2023)
Lung carcinoma (LC) is responsible for almost one-third of all cancer fatalities worldwide. Tetrahydroquinoline is an organic molecule that is the semi-hydrogenated derivative of quinoline and could be found in several naturally occurring compounds such as flindersine, oricine etc. Some tetrahydroquinoline derivatives with pyrazole and hydrazide moieties were evaluated in silico against A549 (human lung cancer cell lines). The quantitative structural-activity relationship (QSAR) model created was statistically significant with validation metrics of R2 (0.9525), R2adj (0.9314), and CV.R (0.9719). The molecular docking analysis revealed that compound C14 demonstrated the best binding affinity towards the studied protein with binding affinity value of –10.1 kcal mol–1 (4LRM). This is in accordance with the experimental result (IC50 = 0.69). The factors observed for ADME&T correlated well with the factors observed for the referenced drug. This study indicates that compounds C1 and C9 can be further developed as anti-epidermal growth factor receptor (EGFR) compounds. Thus, our findings may open door for the design and development of library of efficient Tetrahydroquinoline-based drug-like compounds as potential anti-LC agents.